(De)construction of the mental health care model in the composition of professional practices and services - Quinderé, Paulo Henrique Dias; Jorge, Maria Salete Bessa (Saúde e Sociedade, 2010)
The Brazilian Psychiatric Reform has brought a new vision of treatment and monitoring for people with mental disorders. The creation of the Community Mental Health Centers (Caps) and the insertion of mental health actions in the various levels of complexity of the health system play a major role in the context of the new mental health practices, setting themselves as strategic devices to the transformation of the hospital model. The study aims to discuss the (de)construction of the mental health care model in the city of Sobral, state of Ceará, in the composition of the professional practices and services. This is a historical and social study, carried out in the Integral Mental Health Care Network of the city of Sobral. For data collection we used systematic observation techniques, documents and semi-structured interview. The research participants were defined by theoretical and empirical saturation. The interviews were conducted with ten users, nine workers and four coordinators of mental health services. The results showed that the health care model of the city was reorganized and the mental health actions of the Psychiatric Hospital were allocated in the diverse levels of complexity of the health system. The model of Psychosocial Care provided for people with mental disorders in the city of Sobral has contributed to the transformation of the institutional psychiatric model in the composition of knowledge and practice in mental health.